2003
DOI: 10.1021/tx025599q
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Capsaicin by Cytochrome P450 Produces Novel Dehydrogenated Metabolites and Decreases Cytotoxicity to Lung and Liver Cells

Abstract: Capsaicin is a common dietary constituent and a popular homeopathic treatment for chronic pain. Exposure to capsaicin has been shown to cause various dose-dependent acute physiological responses including the sensation of burning and pain, respiratory depression, and death. In this study, the P450-dependent metabolism of capsaicin by recombinant P450 enzymes and hepatic and lung microsomes from various species, including humans, was determined. A combination of LC/MS, LC/MS/MS, and LC/NMR was used to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
131
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(145 citation statements)
references
References 51 publications
13
131
0
Order By: Relevance
“…This provides a plausible explanation for the toxicity of this analog, but lack of attenuation of cell death at 25 M in both TRPV1-OE and BEAS-2B cells by NAC suggests that TRPV1 must still be involved in some way, as suggested by the correlation studies. The substantially lower toxicity of the diol in NHBE cells also suggests a fundamental difference in reactive oxygen species/ electrophile detoxification capacity between immortalized and primary lung cells, which is important because N- (3,4-dihydroxybenzyl)nonanamide is efficiently produced by CYP1A2 and CYP2C19 (Reilly et al, 2003a;Reilly and Yost, 2006) and, thus, it may be difficult to modulate capsaicinoid toxicity in the intact lung using TRPV1 antagonists alone. Currently, an explanation for the toxicity of N-(4-hydroxybenzyl)nonanamide, 3-methoxy-4-(nonamidomethy)phenyl sulfate, and N-(3-methoxybenzyl) nonanamide is not apparent, but metabolism by cytochromes P450 by hydroxylation to produce nonivamide or N- (3,4-dihydroxybenzyl)nonanamide does not seem to be operative.…”
Section: Discussionmentioning
confidence: 99%
“…This provides a plausible explanation for the toxicity of this analog, but lack of attenuation of cell death at 25 M in both TRPV1-OE and BEAS-2B cells by NAC suggests that TRPV1 must still be involved in some way, as suggested by the correlation studies. The substantially lower toxicity of the diol in NHBE cells also suggests a fundamental difference in reactive oxygen species/ electrophile detoxification capacity between immortalized and primary lung cells, which is important because N- (3,4-dihydroxybenzyl)nonanamide is efficiently produced by CYP1A2 and CYP2C19 (Reilly et al, 2003a;Reilly and Yost, 2006) and, thus, it may be difficult to modulate capsaicinoid toxicity in the intact lung using TRPV1 antagonists alone. Currently, an explanation for the toxicity of N-(4-hydroxybenzyl)nonanamide, 3-methoxy-4-(nonamidomethy)phenyl sulfate, and N-(3-methoxybenzyl) nonanamide is not apparent, but metabolism by cytochromes P450 by hydroxylation to produce nonivamide or N- (3,4-dihydroxybenzyl)nonanamide does not seem to be operative.…”
Section: Discussionmentioning
confidence: 99%
“…It has been further suggested that capsaicin is bioactivated through the formation of several electrophilic metabolites that have the potential to lead to hepatotoxic and/or mutagenic responses Reilly et al 2003;Reilly and Yost 2006). However, the formation of reactive metabolites as identified through in vitro experiments such as glutathione trapping and covalent binding has not been directly linked to adverse drug reactions in the clinic .…”
Section: Metabolism Cyp Inhibition and Antimutagenicitymentioning
confidence: 99%
“…For example, a number of hepatotoxic and non-hepatotoxic compounds have been tested for covalent binding to liver microsomal protein, and the results indicated that prediction of toxicity through the use of in vitro covalent binding experiments was unreliable due to the number of false positive findings (Obach et al 2008). In fact, BEAS-2B and HepG2 cells displayed a greater sensitivity to cytotoxicity in the presence of capsaicin and 1-aminobenzotriazole (a nonspecific CYP450 inhibitor), indicating that capsaicin metabolism represented a detoxification mechanism, as opposed to bioactivation (Reilly et al 2003).…”
Section: Metabolism Cyp Inhibition and Antimutagenicitymentioning
confidence: 99%
“…Hence, even if the consumption of hot pepper is indeed driven by the thermoregulatory effects of CAP, it is unclear whether the driving mechanism is an acute increase in heat loss or a chronic deactivation of neural pathways for heat-defense mechanisms. Furthermore, CAP is metabolized by the liver, and the oral administration of this vanilloid (which delivers CAP to the liver via the portal circulation) is poorly suited for achieving high concentrations in the nervous system (Donnerer et al, 1990;Reilly et al, 2003). It is plausible that people living in hot climates consume more spicy foods simply because more spicy plants grow in such climates and are, therefore, available for greater consumption.…”
Section: Observations In Humansmentioning
confidence: 99%